Electrophysiological markers of cognitive deﬁcits in Traumatic Brain Injury: A review - ROBERTSON, IAN H; DOCKREE, PAUL MICHAEL (My University, 2011)
Event-related potentials (ERPs) and oscillatory activity from the human electroencephalogram (EEG) provides a rich source of data that help elucidate specific processing impairments in TBI patients. This review will focus on some of the central and disabling cognitive deficits in TBI and how broadband ERPs markers and the spectral content of the EEG can help explain abnormalities in brain function that impact upon processing speed, sustained attention, performance monitoring, inhibitory control and cognitive flexibility. Physiological signals also provide useful outcome markers in cognitive intervention studies in conjunction with behavioural endpoints. Potential rehabilitation approaches utilising electrophysiological markers of recovery are also discussed. Progress has been made in recent years in defining key pathophysiological mechanisms in the context of sensitive laboratory paradigms. However, aberrant physiological signals need to be understood more clearly in future studies in terms of the neuroanatomical impact of injury, particularly in relation to the most common type of damage in TBI, disrupting extended white matter fibres.
PUBLISHED
Keywords: Neuroscience; Traumatic Brain Injury